All‐Optical Switchable Vanadium Dioxide Integrated Coding Metasurfaces for Wavefront and Polarization Manipulation of Terahertz Beams. Issue 1 (18th November 2019) - Li, Jie; Yang, Yue; Li, Jining; Zhang, Yating; Zhang, Zhang; Zhao, Hongliang; Li, Fuyu; Tang, Tingting; Dai, Haitao; Yao, Jianquan
Abstract: Electromagnetic metasurfaces are artificial 2D structures with sub‐wavelength size and have achieved a variety of functions. Coding metasurfaces or programmable metasurfaces are special phase‐manipulation type metasurfaces, which can be used for dynamic electromagnetic modulation and information processing in microwave band. However, programmable or tunable coding metasurfaces in terahertz band are still rare. All‐optical switchable coding metasurfaces based on vanadium dioxide (VO2 ) hybrid resonators are proposed for dynamic modulation of terahertz waves. The C‐shaped metal–VO2 hybrid resonators are switched from anisotropic structures to quasi‐isotropic ones due to insulator–metal transition of VO2, resulting in great attenuation of conversion efficiency for linearly polarized waves and Pancharatnam–Berry phase for circularly polarized waves. Based on this principle, several coding metasurfaces are shown for efficient and simultaneous switching of wavefront and polarization state of terahertz beams, including linearly and circularly polarized waves. It is worth mentioning that a new method for switchable shared‐aperture metasurfaces is also proposed, in which only a part of the unit cells are integrated with VO2 and tunable. This new scheme promotes the applications of terahertz coding metasurfaces such as high‐speed terahertz communication. Abstract : All‐optical switchable coding metasurfaces for simultaneous control of polarization state and wavefront of reflected terahertz waves are proposed. The anisotropic and quasi‐isotropic state of the hybrid coding particles can be switched by insulator–metal phase transition of VO2, leading to changes in polarization state and wavefront of the reflected terahertz beams.